STAGED TREATMENT OF COMPLEX THORACOABDOMINAL ANEURYMS FOLLOW TYPE B CHRONIC DISSECTION - Catarino, Joana (2019)
Introduction: Most thoracoabdominal aneuryms (AATA) have a degenerative etiology, non the least, about 20% can be a consequence of chronic dissection, and from those, 40% will require surgical treatment regardless the initial optimal medical treatment. Clinical case: Male patient, 68 years old, with previous history of hypertension and smoker. Angio TC showed a chronic aortic dissection with a complex thoracoabdominal aneuryms and the patient was proposed to a surgical hybrid solution. The first surgery was a Frozen Elephant Trunk followed, days later, by a thoracic endograft to the celiac trunk with distal extension with a dissection stent. Then, a thoracooabdominal endograft (Zenith® t-Branch®). The post operative period was without complications and the follow-up CT showed the normal patency of all endografts and no endoleaks. Conclusion: Staged endovascular treatment of complex AATA looks promising specially when it comes to lower morbidity rates. However, these results can vary depending on patient selection and surgeon skills. Also important is the fact that long term outcomes of such therapy in these specific group of patients are not yet established so, cautious follow-up is needed.